Analisis kesediaan membayar dan kesediaan menerima tata kelola bencana banjir pada daerah aliran Sungai Wosi - Frits Edwin Purba; Rully N Wurarah; David Victor Mamengko (Program Pascasarjana Universitas Papua, 2023)
Wosi is a sub-district located in Manokwari Regency and is a part of the Wosi River Alisan Area (DAS) which has vulnerability to forest cover due to the conversion of settlements and trade centers. Based on this, it is necessary to mitigate the flood disaster structure or carry out flood risk management. One of the government's efforts or policies in flood risk management in Wosi Village is to restore the function of the Wosi watershed through relocation. The Willingness to Pay (WTP) and Willingness to Accept (WTA) approaches related to relocation problems can estimate the WTP and WTA values so that they can optimize the form of policies in reducing flood risk. The results of the analysis show that first, Willingness to Pay flood disaster management through relocation is significantly influenced by education level, income, number of dependents, length of stay and area of residence. Willing to accept a compensation fund of approximately Rp. 32,000,000 to Rp. 506.666,666 and Total WTA is around 1,096,000,000. WTP funds that are willing to be paid are Rp. 82,655,533 (Average WTP) and Rp. 2,479,666,000 (Total value of WTP). The amount of Willingness to Accept is smaller than Willingness to Pay, proving that the paired comparison method can reduce the WTA-WTP gap. In addition, the community's understanding of flood risk reduction in the Wosi watershed is still not optimal, so that the efforts of all parties, especially the local government, in carrying out various policies, plans, and programs that can contribute to risk reduction.